(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In the world of innovative materials, ceramics play an important role due to their wide range of properties. Ceramic technology is based on the processes of preparing ceramic masses, molding raw semi-finished products and thermal bonding. The development of a ceramic structural material that combines high strength and heat resistance has always been very relevant.